A COMPARATIVE STUDY FOR HYPERSPECTRAL DATA CLASSIFICATION WITH DEEP LEARNING AND DIMENSIONALITY REDUCTION TECHNIQUES - Ortaç, Gizem; Özcan, Gıyasettin (My University, 2018)
In recent years, hyperspectral imaging has been a popular subject in the remote sensing community by providing a rich amount of information for each pixel about fields. In general, dimensionality reduction techniques are utilized before classification in statistical pattern-classification to handle high-dimensional and highly correlated feature spaces. However, traditional classifiers and dimensionality reduction methods are difficult tasks in the spectral domain and cannot extract discriminative features. Recently, deep convolutional neural networks are proposed to classify hyperspectral images directly in the spectral domain. In this paper, we present comparative study among traditional data reduction techniques and convolutional neural network. The obtained results on hyperspectral image data sets show that our proposed CNN architecture improves the accuracy rates for classification performance, when compared to traditional methods by increasing the classification accuracy rate by 3% and 6%.

;Son yıllarda, hiperspektral görüntüleme yüzey pikselleri ile ilgili zengin miktarda bilgi sağlamasıyla uzaktan algılama alanında popüler bir konu olmuştur. Genel olarak, elde edilen yüksek boyutlu ve ilişkisel veriyi işlemek için, sınıflandırmadan önce boyut indirgeme teknikleri uygulanmaktadır. Bununla birlikte geleneksel sınıflandırıcılar ve boyut azaltma yöntemleri, spektral alanda hala zorlu bir işlemdir ve ayırt edici öznitelikler çıkarmaz. Son zamanlarda ise derin konvolüsyonel sinir ağları, hiperspektral görüntüleri doğrudan spektral alanda sınıflandırmak için geliştirilmiştir. Önerilen çalışmada, geleneksel sınıflandırma ve konvolüsyonel sinir ağları arasında karşılaştırmalı bir çalışma ve analiz yapılmıştır. Çeşitli hiperspektral görüntü verilerine dayanarak elde edilen sonuçlar, önerilen konvolüsyonel sinir ağının, geleneksel yöntemlerden %3 ve %6 oranında daha iyi bir sınıflandırma oranı sağladığını göstermiştir.
Hiperspektral Verilerin Sınıflandırmasında Derin Öğrenme ve Boyut İndirgeme Tekniklerinin Karşılaştırılması
Keywords: Bilgisayar Bilimleri, Bilgi Sistemleri; Bilgisayar Bilimleri, Yazılım Mühendisliği; Mühendislik, Kimya; İnşaat Mühendisliği; Mühendislik, Elektrik ve Elektronik; Çevre Mühendisliği; Mühendislik, Jeoloji; Endüstri Mühendisliği; İmalat Mühendisliği; Mühendislik, Makine; Malzeme Bilimleri, Özellik ve Test; Metalürji Mühendisliği